Microecology of pyodermia pathogens - V. Stepan; N. Stepan; B. Stepan (Journal of Education, Health and Sport)
Gram-positive cocci are usually considered the leading pathogens of pyoderma. However, understanding intermicrobial interactions, as well as identifying the leading pathogens and their associates, require a more detailed study of microbial contamination of the skin other than a simple statement of the taxonomic composition of the microbial community of the biofilm. The aim of this study is to determine the microecological indicators of pyoderma pathogens.